Association Between Growth Differentiation Factor-15 and Heart Failure Complicating Acute Myocardial Infarction - Meloux, Alexandre; Rochette, Luc; Maza, Maud; Bichat, Florence; Cottin, Yves; Zeller, Marianne; Vergely, Catherine (Cardiology and Cardiovascular Medicine, 2020)
Background - Growth differentiation factor-15 (GDF15) is an emerging biomarker in cardiovascular diseases. We aimed to evaluate the association of GDF15 levels at admission with HF occurrence during hospitalization for acute myocardial infarction (AMI). Methods - Our prospective study included all patients admitted from June 2016 to February 2018 for type 1 AMI in the coronary care unit of the Dijon-Bourgogne University Hospital. In-hospital severe heart failure (HF) was defined as Killip class >2. Serum levels of GDF15 were obtained from blood samples were taken on admission. Results – Among the 284 AMI patients, median age was 67 years, and 27% were women. GDF15 levels were strongly correlated with age and positively correlated with most cardiovascular risk factors (hypertension and diabetes) and inflammation (CRP>3 mg/L). When compared with patients without HF (274/284), GDF15 in patients with in-hospital HF (10/284) was more than two times higher. Multivariate regression showed that GDF15 >5,000 ng/L was an independent marker of HF. Conclusions - These results suggest that GDF15 could be an integrative biomarker for severe in-hospital HF in patients with AMI. Further studies are needed to elucidate the underlying mechanisms linking this cytokine to the development of HF. Clinical Trial BIOCARDIS - 2016 – 9205AAO034S02117, from June 2016 to February 2018